2017
DOI: 10.1371/journal.pone.0171393
|View full text |Cite
|
Sign up to set email alerts
|

Binge drinking during adolescence and young adulthood is associated with deficits in verbal episodic memory

Abstract: Binge drinking (BD), a harmful pattern of alcohol consumption, is common during adolescence. Young adults with alcohol use disorders exhibit hippocampal alterations and episodic memory deficits. However, it is not known how these difficulties progress in community BD adolescents. Our objective was to analyze the relationship between BD trajectory and verbal episodic memory during the developmental period spanning from adolescence and to early adulthood. An initial sample of 155 male and female first-year unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 68 publications
2
47
0
5
Order By: Relevance
“…The recent systematic review of neuropsychological studies in young people reported that the binge drinking pattern is associated with cognitive difficulties, especially with lower performance in verbal memory and executive deficits [20]. The results provided by our group over the last decade show difficulties in performing tasks that involve inhibitory control, cognitive interference, working memory and episodic declarative verbal memory-functions dependent on frontolymbic and frontoparietal areas [3,[20][21][22][23][24][25]. Finally, recent literature reaffirms the need for a systematic examination of the gender variable.…”
Section: Alcohol Consumption In Youth and Consequences In Early Adultmentioning
confidence: 62%
“…The recent systematic review of neuropsychological studies in young people reported that the binge drinking pattern is associated with cognitive difficulties, especially with lower performance in verbal memory and executive deficits [20]. The results provided by our group over the last decade show difficulties in performing tasks that involve inhibitory control, cognitive interference, working memory and episodic declarative verbal memory-functions dependent on frontolymbic and frontoparietal areas [3,[20][21][22][23][24][25]. Finally, recent literature reaffirms the need for a systematic examination of the gender variable.…”
Section: Alcohol Consumption In Youth and Consequences In Early Adultmentioning
confidence: 62%
“…Longitudinal studies have indicated the adverse influence of adolescent heavy drinking not only on the development of visuospatial processing but also on attention and working memory development (Carbia, Cadaveira, Caamano-Isorna, Rodriguez-Holguin, & Corral, 2017;Hanson, Medina, Padula, Tapert, & Brown, 2011;Squeglia, et al, 2009;Tapert, Granholm, Leedy, & Brown, 2002). Accordingly, poor academic performance (Hanson, et al, 2011) and executive function impairments (Goudriaan, Grekin, & Sher, 2007;Scaife & Duka, 2009) have been observed in adolescents with alcohol abuse.…”
Section: F I Nd I Ng S I N Hu M a N Stu D I Esmentioning
confidence: 99%
“…A body of research evidences the relationship between alcohol consumption, and the deterioration of cognitive functions and worsening academic performance. For example, excessive alcohol consumption is associated with disorders of memory, attention, and planning [12][13][14][15][16][17]; daily drinking was significantly negatively associated with academic performance [18]; and problematic alcohol use among university students was associated with poor academic performance [19]. The relationship between HED and academic engagement, performance, and future aspirations among secondary school students suggests that students who initiate binge drinking have poor school performance and engagement, which may hinder achieving their future academic goals [20].…”
Section: Introductionmentioning
confidence: 99%